Effect of zinc oxide nanoparticles synthesized from Carya illinoinensis leaf extract on growth and antioxidant properties of mustard (Brassica juncea) - Geremew, Addisie; Carson, Laura; Woldesenbet, Selamawit; Wang, Huichen; Reeves, Sheena; Brooks, Nigel; Saganti, Premkumar; Weerasooriya, Aruna; Peace, Elisha (Frontiers in Plant Science, 2023)
The sustainability of crop production is impacted by climate change and land degradation, and the advanced application of nanotechnology is of paramount importance to overcome this challenge. The development of nanomaterials based on essential nutrients like zinc could serve as a basis for nanofertilizers and nanocomposite synthesis for broader agricultural applications and quality human nutrition. Therefore, this study aimed to synthesize zinc oxide nanoparticles (ZnO NPs) using pecan (Carya illinoinensis) leaf extract and investigate their effect on the growth, physiology, nutrient content, and antioxidant properties of mustard (Brassica juncea). The ZnO NPs were characterized by UV-Vis spectrophotometry, Dynamic Light Scattering (DLS), X-ray diffractometer (XRD), Scanning Electron Microscopy (SEM), and Fourier Transform Infra-Red Spectroscopy (FTIR). Mustard plants were subjected to different concentrations of ZnO NPs (0, 20, 40, 60, 80, 100 and 200 mg L-1) during the vegetative growth stage. The UV-Vis spectra of ZnO NPs revealed the absorption maxima at 362 nm and FTIR identified numerous functional groups that are responsible for capping and stabilizing ZnO NPs. DLS analysis presented monodispersed ZnO NPs of 84.5 nm size and highly negative zeta potential (-22.4 mV). Overall, the application of ZnO NPs enhanced the growth, chlorophyll content (by 53.37 %), relative water content (by 46.7%), shoot biomass, membrane stability (by 54.5 %) and net photosynthesis significantly in a dose-dependent manner. In addition, the supplement of the ZnO NPs augmented K, Fe, Zn and flavonoid contents as well as overcome the effect of reactive oxygen species by increasing antioxidant capacity in mustard leaves up to 97.3%. In conclusion, ZnO NPs can be potentially used as a plant growth stimulant and as a novel soil amendment for enhancing crop yields. Besides, the biofortification of B. juncea plants with ZnO NPs helps to improve the nutritional quality of the crop and perhaps potentiates its pharmaceutical effects.